Determinants of export pricing at the firm-level: evidence from Egypt. Issue 8 (17th November 2021) - Kamal, Yasmine
Abstract : The study explains the export pricing behaviors of Egyptian firms using detailed customs data and high-dimensional fixed effects. Firstly, it finds that more productive firms (as proxied by firms' importation of intermediate inputs and capital goods) charge higher export prices which are correlated with higher revenues, providing an evidence for competition in quality, rather than price, amongst firms. Secondly, firms with more destinations charge a higher price for their exported products and a wider price range across markets. Thirdly, firms charge higher prices for more distant and richer destinations, whereas they charge lower prices for larger-sized and less central ones. This could be explained by variable mark-ups across destinations, where higher mark-ups are set in more distant, richer, smaller (less competitive), and more central destinations. It could also indicate that higher quality product versions are sent to more distant destinations (Alchian-Allen or selection effects) and richer ones (demand effect). Lastly, firms charge higher prices for destinations with a larger prevalence of technical measures or those imposing specifically restrictive ones, potentially reflecting an adverse effect of these measures on the number of exporting firms, allowing survivors to charge higher mark-ups. Alternatively, this could reflect firms' quality upgrading in compliance with such measures.